Post-apocalyptic Subjectivity and Nature/Culture Duality in Lois Lowry’s The Giver (ENTHYMEMA, 2023)
The present inquiry endeavors to scrutinize the process of identity formation with regard to the Culture/Nature dichotomy within the milieu of Lois Lowry's post-apocalyptic dystopian narrative, The Giver. The antipodal forces of Culture and Nature are instrumental in shaping the social subjectivities of individuals. Lowry's post-apocalyptic dystopia portrays a society in which these antitheses are comprehensively epitomized. Our objective is to explicate the genesis of post-apocalyptic identities and to elucidate the representation of Nature/Culture within the social context of the aforementioned literary work. Furthermore, the polarity between power and resistance, which is of notable import to cultural studies, is nonexistent within this post-apocalyptic dystopia. Consequently, the establishment of identities transpires not at the site of contention between power and resistance, but exclusively through the ascendency of the imperializing power. As a corollary, the elimination of the recollections of those individuals who are unable to oppose the imperializing power is integral to the construction of homogeneous identities.
Keywords: Post-apocalyptic Identity; Culture/Nature Duality; Imperialising Power; Cultural Studies; Docile Bodies